A 15-year-old boy with an unerupted tooth enclosed by dentigerous cyst associated with odontome: Dentigerous cyst associated with odontome (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Odontoma are the most common benign odontogenic tumor of epithelial and mesenchymal origin. Usually a conservative approach is the standard treatment protocol for this. Odontoma associated with unerupted tooth andodontogenic cyst aggravates the existing condition. Generally, expansible nature of cystic lesions require surgical excision which is different from isolated non-symptomatic odontomas that can be monitored by periodic radiological examination. There is inadequate evidence on the presence of odontoma-associated cystic lesions in the oral cavity. Therefore, the present case report is aimed at describing the diagnostic clinical, radiological, and histological features together with the surgical management of a dentigerous cyst associated with a compound odontoma. The lesion was surgically removed. No recurrence was observed after 12 months of follow-up.BSMMU J 2022; 15(3): 201-203